Relationship between parental involvement, academic resilience, and academic stress among adolescents in Kuala Terengganu - Ramlan, Noor Yasmin; Ahmad, Sa’odah (Human Resources Management Academic Research Society (HRMARS), 2023)
The study aimed to determine the relationship between parental involvement, academic resilience, and academic stress among adolescents in Kuala Terengganu. A total of 261 students participated in this study, and they were chosen by using a multi-stage cluster random sampling technique. The data were collected through a set of self-administered questionnaires. Parental Support for Learning Scale: Adolescent (Rogers et al., 2014), The Academic Resilience Scale (Cassidy, 2014), and the Academic Expectation of Stress Inventory (Ang & Huan, 2006) were used to measure parental involvement, academic resilience, and academic stress respectively. The results showed that the adolescents experienced high parental involvement, high academic stress, and low academic resilience. Parental involvement and academic resilience correlated significantly with the academic stress of adolescents. The relative strength of antecedent variables and independent variables in predicting academic stress was analyzed using multiple regression analysis. It was revealed that parental involvement was the strongest predictor of academic stress. This finding concurs with the results of past research that have shown that students’ academic stressors are identified in the family and school environments. Thus, due consideration should be given to family and school environment aspects in any effort or intervention related to adolescents’ academic stress management.